Theoretical studies on thermally activated delayed fluorescence mechanism of a series of organic light‐emitting diodes emitters comprising 2, 7‐diphenylamino‐9, 9‐dimethylacridine as electron donor. Issue 31 (23rd October 2018) - Feng, Songyan; Wen, Keke; Si, Yubing; Guo, Xugeng; Zhang, Jinglai
Abstract : According to one experimentally reported thermally activated delayed fluorescence (TADF) emitter (AcDPA‐2TP ), two new molecules (AcDPA‐2PP andAcDPA‐TPP ) have been designed theoretically to probe into the effect of different acceptor strengths on their TADF mechanisms. In this work, the rates of reverse intersystem crossing ( k RISC ) of the three targeted molecules were calculated by the semiclassical Marcus rate expression. The present results demonstrate that the k RISC rate ofAcDPA‐2PP is estimated to be 5.56 × 10 6 s −1, about twice larger than that ofAcDPA‐2TP (2.63 × 10 6 s −1 ), and especiallyAcDPA‐TPP is found to exhibit the largest k RISC value (6.97 × 10 6 s −1 ) among the three molecules. Considering thatAcDPA‐2TP has been observed to be an efficient TADF emitter, our newly designed two moleculesAcDPA‐2PP andAcDPA‐TPP are also expected to be potential TADF materials. © 2018 Wiley Periodicals, Inc. Abstract : Three thermally activated delayed fluorescence (TADF) emitters were studied theoretically, whereAcDPA‐2TP is an experimentally reported molecule, andAcDPA‐2PP andAcDPA‐TPP are two theoretically designed molecules. Calculations reveal that the reverse intersystem crossing rates follow the order ofAcDPA‐TPP > AcDPA‐2PP > AcDPA‐2TP. Considering thatAcDPA‐2TP has been observed to be an efficient TADF emitter, AcDPA‐2PP andAcDPA‐TPP are also expected to be potential TADF materials.